INTEGRATION OF POKA YOKE INTO PROCESS FAILURE MODE AND EFFECT ANALYSIS: A CASE STUDY - A. P., Puvanasvaran; Jamibollah, N; N., Norazlin (Science Publication, 2014)
The Failure Mode and Effect Analysis (FMEA) is a one of the requirements which was required by the Automotive Industries Action Group (AIAG) to all the automotive suppliers and manufacturers worldwide through the TS16949 Quality System. There were a lot of dicrepencies detected on implementing the FMEA which directly related to the user experinces and knowledge. The descrepencies cause the FMEA not meeting the objectives of it. Conceptually, Poka Yoke is able to fit into the Process FMEA. Failure Mode and Effect Analysis (FMEA) helps predict and prevent problems through proper control or detection methods. Mistake proofing emphasizes detection and correction of mistakes before they become defects. Poka Yoke helps people and processes work correctly the first time. It refers to techniques that make mistakes impossible to commit. These techniques eliminate defects from products and processes as well as substantially improve their quality and reliability. Poka Yoke can be considered an extension of FMEA. The use of simple Poka Yoke ideas and methods in product and process design eliminates both human and mechanical errors. Ultimately, both FMEA and Poka Yoke methodologies result in zero defects and benefit either the end or the next-in-line customer. The first concept of Poka Yoke emphasizes elimination of the cause or occurrence of the error that creates the defects by concentrating on the cause of the error in the process. The defect is prevented by stopping the line or the machine when the root cause of the defect is triggered or detected. The second concept of Poka Yoke focuses on the effectiveness of the detection system. The foolproof detection system eliminates the defect or detects the error that causes defects. The implementation of the Poka Yoke concept in a foolproof detection system eliminates the possibility that error or defects will slip through the process and reach the customer.